Avaliação do efeito antifibrótico hepático do bezafibrato em modelos in vitro e in vivo de fibrose hepática - Reghelin, Camille Kirinus (2022)
Hepatic fibrosis (FH) is characterized by the healing process that represents the hepatic response to injuries, through the deposition of collagen and other constituents of the extracellular matrix. This process occurring repeatedly can culminate in liver cirrhosis, in which the architectural organization of the liver changes to the point of interfering with blood flow and its functions. Among the most serious complications of the disease, this included portal hypertension, liver failure and cancer. The main cells involved in hepatic fibrosis that produce extracellular matrix are hepatic stellate cells. This population of resident cells contains a quiescent phenotype that functions as the body's vitamin A store. And when activated, they transform to adopt a myofibroblast phenotype. The present study sought new treatment options based on concepts already applied, established and related to drug repositioning, in which we directed our analysis to bezafibrate. This is a drug commonly used to reduce the levels of cholesterol and triglycerides in the blood, acting through the activation of Peroxisome proliferator-activated receptors (PPARs). Therefore, we sought to verify the potential antifibrotic effect of BZF in experimental models in vitro and in vivo. as a possible new therapy for the treatment of liver fibrosis. The parameters evaluated in vitro were cell proliferation, cytotoxicity index, identification of acidic vesicular organelles (AVOs), quantification of lipid droplets, collagen gel contraction and analysis of molecular markers related to phenotypic activation and reversion. Subsequently, hepatic injury markers was investigated in vivo, as well as histological and molecular aspects. After 72 hours of in vitro treatment, BZF decreased cell proliferation, reversed phenotype, reduced cell contraction and induced autophagy. In addition, BZF demonstrated a protective effect on tetrachloride-induced liver fibrosis in mice, confirmed by serum, liver tissue and molecular analysis.